Mengembangkan Aspek Sosial/Kerjasama Siswa Melalui Metode Wisata TK Tirodeceng Pompanua Kabupaten Bone - rukayah rukayah (Universitas Negeri Makassar, 2019)
This study aims to determine the completeness of students in understanding the material in collaboration with students and efforts to improve learning outcomes in collaboration with students using the field trip method. This research is a type of classroom action research. The approach used is a qualitative approach. The subjects in this study were the students of TK Tirodeceng Pompanua in the 2017/2018 academic year, totaling 17 people. The object in this study is the use of field trips in increasing motivation to learn student cooperation and creativity. The tools used to collect data are tests, interviews, and observations. This study consisted of two cycles. Efforts are made to understand the material of collaboration, researchers provide learning in groups using teaching aids accompanied by demonstrations. Giving action by learning using the field trip method in the first and second cycles obtained the average value and level of student learning completeness. In the initial test, the students' average score was 1.94, when the test post I the student's average score increased to 3.18 and at the time of the test post-II the student's average score increased to 3.23 with a learning completeness level of 88%. It means that the results obtained by students at the test post II have reached the level of completeness in a classical manner, namely at least 85% of students who get a value of ≥ 3 stars.